P57 Filling the gap for children with heart failure: the EU-funded drug development program LENA (labeling of enalapril from neonates up to adolescents). Issue 6 (17th May 2019) - Laeer, S; Breitkreutz, J; Klingmann, I; Lagler, F; Dalinghaus, M; Bajcetic, M; de Wildt, S; Clark, AK; Breur, H; Male, C; Jovanovic, I; Djukic, M; et al.
Abstract : Background: ACE-inhibitors are first choice treatment for adult and paediatric patients with heart failure. Since there are no systematic data on pharmacokinetics and safety in the young heart failure population, the EU funded a drug development program 1 to fill those gaps for the ACE-inhibitor enalapril. An age appropriate paediatric formulation was also required. Methods: A paediatric patient cohort with heart failure was recruited to fulfil the paediatric investigation plan (PIP) requirements. The PIP required a total of 85 evaluable patients from birth to less than 12 years of age with a subset cohort of 25 patients with heart failure due to dilated cardiomyopathy and a subset of 60 heart failure patients of congenital heart disease. Out of these, 54% of patients must be aged below 12 months to provide a substantial amount of young patients. Results: The LENA consortium recruited 102 children from birth to 12 years. Out of those, 89 patients fulfilled relevant protocol criteria and could be regarded as evaluable. Of these, 26 demonstrated heart failure due to cardiomyopathy and 63 due to congenital heart disease. Sixty five patients (73%) were below 12 months of age. Moreover, 22 patients were below 3 months of age, 26 patients from 3 months to less than 6 months and 17 patients from 6 months up to 12 months of age. Conclusions: The LENA consortium had recruited the PDCO required number of paediatric patients for the drug development program LENA. As more than 2/3 of patients belong to the most vulnerable patient population below the age of 12 months, relevant data can be generated to fill gaps for the safe and reliable treatment with ACE-inhibitors of children with heart failure. References: The research leading to these results has received funding from the European Union Seventh Framework Programme (FP7/2007–2013) under grant agreement n°602295 (LENA) Disclosure(s): Nothing to disclose